A systematic review of help-seeking and mental health service utilization among military service members. (April 2017) - Hom, Melanie A.; Stanley, Ian H.; Schneider, Matthew E.; Joiner, Thomas E.
Abstract: Research has demonstrated that military service members are at elevated risk for a range of psychiatric problems, and mental health services use is a conduit to symptom reduction and remission. Nonetheless, there is a notable underutilization of mental health services in this population. This systematic review aimed to identify and critically examine: (1) rates of service use; (2) barriers and facilitators to care; and (3) programs and interventions designed to enhance willingness to seek care and increase help-seeking behaviors among current military personnel (e.g., active duty, National Guard, Reserve). Overall, 111 peer-reviewed articles were identified for inclusion. Across studies, the rate of past-year service use among service members with mental health problems during the same time frame was 29.3% based on weighted averages. Studies identified common barriers to care (e.g., concerns regarding stigma, career impact) and facilitators to care (e.g., positive attitudes toward treatment, family/friend support, military leadership support) among this population. Although programs (e.g., screening, gatekeeper training) have been developed to reduce these barriers, leverage facilitators, and encourage service use, further research is needed to empirically test the effectiveness of these interventions in increasing rates of service utilization. Critical areas for future research on treatment engagement among this high-risk population are discussed. Highlights: Military personnel with psychiatric problems underutilize mental health services. Stigma and career concerns are commonly reported barriers to care. Support from military leadership and peers may facilitate help-seeking. Evidence-based interventions to enhance service use are lacking for this population.